A multi-wavelength view of the cosmic ray confinement in star-forming galaxies - Kornecki, Paula (2021)
Cosmic rays (CRs) are responsible for a tight correlation between the star formation rate (SFR)and the radio/W-ray luminosity observed in star-forming galaxies (SFGs). This correlation canbe explained by a linear scaling between the SFR and the number of CR acceleration sites, suchas supernova remnants, coupled to the dependence of particle escape with galaxy properties.Observations in radio and W-rays are important tools to probe CR activity, but they may not besufficient to fully characterise the confinement properties of galaxies. For instance, CR calorimetryis one of the most intriguing unanswered aspects in star-forming regions that could result not onlyin emission through the neutrino channel but possibly also in the hard X-ray and MeV energybands. We perform a multi-wavelength investigation of the CR population and the effective fieldsaffecting their transport within SFGs with different levels of activity. In particular, we focus on thepossibility of testing proton confinement in the X-ray and MeV bands. With this goal, we developa model describing the CR transport in SFGs for a broad range of SFRs. Hadronic byproducts, pairproduction and leptonic emission are computed self-consistently in a multi-wavelength contextranging from radio up to X-rays and W-rays. We conclude that a panchromatic view of the SFR?luminosity correlations in SFGs is key to place strong constraints on the physical processes thatgovern the non-thermal physics of these sources.